Interactive optimization tool for the optimum design of helical extension springs. - Galeano, Carlos; Duque, Carlos; Tovar, Andrés (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This work presents an interactive computer tool for the optimal design of helical extension springs. The developed algorithm incorporates all design considerations used in the manufacturing industry and specialized design manuals. All these considerations are used to create a novel optimum design formulation. The flexibility of this software allows the user to characterize a particular design problem, through the selection of the right constraints for each case. The optimization model includes sixteen constraints (linear and nonlinear) derived from different failure criteria and designs and manufacture recommendations. This nonlinear problem is solved using sequential quadratic programming in Matlab. The characteristics of this tool are showed through development of a benchmark problem. The free software developed in this work is available at http://www.unal.edu.co/optimun/resortes/.